Cyber Threat in Drone Systems: Bridging Real-Time Security, Legal Admissibility, and Digital Forensic Solution Readiness - Mohammed, Usman Mistura; Omolara, Abiodun Esther; Abiodun, Oludare Isaac; Rasheed, Jawad; Osman, Onur; Lar, Patricia Manko; Adeyinka, Philip Oyadiran; Olugbenga, Adeola Grace; Rasheed, Jawad (Frontiers Media SA, 2025)
The rapid expansion of drones otherwise known as Unmanned Aerial Vehicles(UAVs), in critical sectors has increased their exposure to cyber threats such asGPS spoofing, command hijacking, andfirmware tampering. Existing forensictools often fail to address UAV-specific challenges like volatile memory andlimited storage, hindering effective investigations. Hence, to address this gap, thisstudy proposes the Enhanced UAV Forensic Framework (EUAVFF) a modular,forensic-by-design model integrating blockchain audit trails, secure logging,telemetry offloading, and UAV-friendly encryption. Validated through aliterature review and a stakeholder survey (n = 100), results showed that over70% of respondents lacked awareness of UAV cyber risks, and current droneswere rated poorly in key forensic areas, including tamper-proof logging and legalevidence handling. Only 28% were familiar with drone-specific threats, reflectingcritical gaps in preparedness.Thesefindings emphasize the urgent need forproactive forensic integration. EUAVFF offers a structured path to secure,accountable, and resilient UAV operations in increasingly hostile cyberenvironments.
Keywords: UAV security threats; UAV digital forensics solution; Forensic readiness; Cybercrimeinvestigation; Forensic framework; Real-time evidence collection